KEEFEKTIFAN STRATEGI OK5R (OVERVIEW, KEY IDEALS, READ, RECORD, RECITE, REVIEW DAN REFLECT) DALAM PEMBELAJARAN MENULIS PARAGRAF EKSPOSISI PADA SISWA KELAS IX SMP NEGERI 42 BULUKUMBA - Andi Paida (Universitas Negeri Makassar, 2016)
Abstract: Effectiveness Strategy OK5R (Overview, Key Ideals, Read, Record, Recite, Review and Reflect) in Paragraph Writing Learning Exposition in Class IX SMPN 42 Bulukumba. This study aims to determine the effectiveness of the strategy OK5R (Overview, Key Ideals, Read, Record, Recite, Review, and Reflect) in Paragraph Writing Learning Exposition in Class IX SMPN 42 Bulukumba. The population in this study consisted of two classes totaling 58 students. Through random sampling techniques and gained 48 students, ie 24 out of the class IXB as an experimental class and 24 students of the class IXa as the control class. The data collection is done by administering a pretest and posttest. Descriptive analysis showed that the average value of student learning outcomes with the experimental class OK5R Strategies (Overview, Key Ideals, Read, Record, Recite, Review, and Reflect) was 68.3 pretest and posttest 81, compared with the control class average value average student learning outcomes pretest posttest 68.3 and 75.4. Based on the results of inferential statistical hypothesis test obtained by using the value of σ (0.05), the H1 is accepted so that it can be concluded that the presence of OK5R Strategies (Overview, Key Ideals, Read, Record, Recite, Review, and Reflect) then learning will be effective.